Инновации для устойчивого развития: обзор по кыргызской республике - United Nations (United Nations, 2020)
This Review contains the outcomes of a policy advisory exercise that drew on the experience accumulated by the UNECE in the identification of good practices and policy lessons in the area of knowledge-based development, with particular reference to the problems of countries with economies in transition, in this case Kyrgyzstan. It provides a set of recommendations and policy options to stimulate innovation activity in the country, enhance its innovation capacity and improve the overall efficiency of the national innovation system.